2018
DOI: 10.1029/2018gl079695
|View full text |Cite
|
Sign up to set email alerts
|

3D Analysis of GW Propagation in the Ionosphere

Abstract: Unique observation and analysis of gravity wave (GW) propagation in the ionosphere was performed on the basis of multipoint and multifrequency continuous Doppler sounding in the Czech Republic. The sounding radio waves of various frequencies reflect at different heights. Thus, the propagation of GWs can be studied in three‐dimensional space using the time (phase) delays between observation of corresponding signatures at different reflection points that are separated both horizontally and vertically. The indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…They are considered to be a regular phenomenon with smaller amplitudes than those LSTIDs generated by auroral activity. Chum & Podolská (2018) also discussed this kind of TIDs and showed that they can propagate in different directions.…”
Section: Applicability Of Indices As Precursors For Lstids Occurrencementioning
confidence: 99%
See 1 more Smart Citation
“…They are considered to be a regular phenomenon with smaller amplitudes than those LSTIDs generated by auroral activity. Chum & Podolská (2018) also discussed this kind of TIDs and showed that they can propagate in different directions.…”
Section: Applicability Of Indices As Precursors For Lstids Occurrencementioning
confidence: 99%
“…LSTIDs propagate with horizontal velocities between 400 and 1000 m/s, horizontal wavelengths greater than 1000 km and periods in the range of 30 min to 3 h (Hunsucker, 1982;Hocke & Schlegel, 1996). Another type of TIDs are the medium-scale TIDs (MSTIDs), which propagate with velocities between 100 and 250 m/s, periods in the range of 10 min to 1 h and wavelengths between 100 and 1000 km (Hunsucker, 1982;Shiokawa et al, 2009;Chum & Podolská, 2018). Mid-latitude MSTIDs are considered to be excited by diverse mechanisms (see Kotake et al, 2006Kotake et al, , 2007Kelley, 2011;Otsuka et al, 2013;Chen et al, 2019) and are out of the scope of this work.…”
Section: Introductionmentioning
confidence: 99%
“…TIDs are only analyzed if condition (1) is fulfilled for more than 80% of data points in the last 90 min. The observed horizontal velocity and azimuth of propagation are then computed from the observed time (phase) delays between signals recorded for different sounding paths (transmitter-receiver pairs) using three different calculation methods described by Chum & Podolská (2018): (i) slowness search; (ii) least squares fitting to the time delays obtained from cross-correlation of the f DCi series; (iii) weighted least squares fitting to the time delays obtained from cross-correlation of the f DCi series; the weights are the maxima of the crosscorrelation functions. Figure 7.…”
Section: Medium Scale Tid Detection Methodologiesmentioning
confidence: 99%
“…Induced disturbance to electron density, N e ′, below the F2 peak [17], is estimated as where |N e ′| is the perturbation magnitude given by and ϕ the phase obtained from (4) It should also be noted that GWs can be attenuated in the F layer because of the higher air viscosity and thermal conductivity [18]. Experimentally, Chum and Podolska [19] observed an average attenuation of 0.14 dB km −1 . However, as a first approximation attenuation is neglected in the present work.…”
Section: Tid Modelmentioning
confidence: 99%